"I feel terrible and need to exercise to find any sort of joy": What COVID stay‐at‐home orders tell us about exercise as vitality politics and entertainment in the United States. (25th December 2022) - Hejtmanek, Katie Rose; Ocobock, Cara
Abstract: During COVID‐19 stay‐at‐home orders (SaHOs), people faced drastic shifts in their work and home lives. These shifts, in combination with the temporary closure of gyms and fitness centers, led to exercise‐routine disruption. We conducted a survey to assess how people were affected by SaHOs in terms of exercise‐routine change, feelings about exercise, perceived physical and mental health, as well as exercise‐routine plans once SaHOs were lifted. In this article, we examine why affluent white American women exercised before and during COVID‐19 SaHOs. The article focuses on the role of pleasure and entertainment as key components of exercise practices for these women. We found that changes in motivation reveal that exercise regimens are part of contemporary vitality politics, or current cultural and subjective desires and abilities to manipulate and optimize biological human processes, that include both health and entertainment. Therefore, we argue that exercise is a meaningful cultural, entertainment, and biopolitical activity.